Suffering people - Balwant Singh (Sahranpur, 2002)
This book deals with the sufferings of the low castes in India.The period of years of Independence has no doubt made a difference in the economic life of the lower classes, but in social terms there has been little change and the low castes in India even today suffer from the age old social disabilities and discrimination.
Keywords: Civil service